3D MODELING OF HEAT TRANSFER PROCESSES IN THE COMBUSTION CHAMBER BOILER OF THERMAL POWER PLANTS - A.S. Askarova; S.A. Bolegenova; P. Safarik; V.Yu. Maximov; A.O. Nugymanova; S.A. Bolegenova (Academic Scientific Journal of Computer Science, 2019)
In the present work, a computer-aided 3D modeling method was used to conduct a comprehensive study of heat and mass transfer processes in turbulent flows of high-temperature reactive media in real geometry. Numerical computations of the thermal processes and aerodynamic characteristics of the flow were made for the combustion chamber of the BKZ-75 boiler at Shakhtinskaya thermal power plant for combustion of high-ash fuel. Using the methods of computer 3D-modeling, we took into account a great number of phenomena and factors affecting the real technological processes in the combustion chambers of industrial facilities. The aerodynamic picture of the studied combustion chamber was obtained, the temperature fields and energy distributions released due to chemical reactions were constructed, and the values of radiation heat fluxes to the main heat-receiving surfaces of the combustion chamber were determined. The results of numerical calculations can be used to design new and modernize existing combustion chambers of industrial boilers working on solid fuel, as they are based on the most advanced physical and mathematical models in this area. The use of modern technologies for 3D numerical computations of solid fuel combustion in the combustion chambers of thermal power plants, will allow us to describe in detail the fields of velocity, temperature, pressure and concentrations of all combustion products and, above all, harmful substances and other characteristics of the coal combustion process throughout the combustion space and at the outlet of the combustion chamber.